2021
DOI: 10.17957/ijab/15.1671
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Induces Differential DNA Methylation Shift at Symmetric and Asymmetric Cytosine Sites in the Promoter Region of ZmEXPB2 Gene in Maize

Abstract: β-expansin 2 (EXPB2) gene induces drought tolerance in different plant species including maize. Different epigenetic mechanisms like DNA methylation, histone modification and RNA interference affect the gene activities under stress conditions. DNA methylation, an important epigenetic mechanism, could be involved in the regulation of ZmEXPB2 gene under drought stress in maize. Plants of drought sensitive variety „Jalal‟ were grown till 4th leaf stage under well-watered conditions. At 5th leaf stage, plants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The proportion of methylation changes in response to drought mostly ranged from 10 to 20%, but some showed only slight changes, which may be related to tissue specificity [144]. In contrast, the proportions and trends of methylation sites in the three contexts were different, with the trends of symmetric methylation sites such as CG and CHG remaining the same, whereas most of the CHH asymmetric methylation sites were opposite to the symmetric methylation sites, which might be more sensitive to drought environment; this was confirmed in the study of Zea mays L. and Populus tomentosa [125,135], although methylation of CG, CHG symmetry sites were more sensitive to drought stress in other species of plants studied [126,143].…”
Section: Tap5cs Tabadhmentioning
confidence: 61%
See 2 more Smart Citations
“…The proportion of methylation changes in response to drought mostly ranged from 10 to 20%, but some showed only slight changes, which may be related to tissue specificity [144]. In contrast, the proportions and trends of methylation sites in the three contexts were different, with the trends of symmetric methylation sites such as CG and CHG remaining the same, whereas most of the CHH asymmetric methylation sites were opposite to the symmetric methylation sites, which might be more sensitive to drought environment; this was confirmed in the study of Zea mays L. and Populus tomentosa [125,135], although methylation of CG, CHG symmetry sites were more sensitive to drought stress in other species of plants studied [126,143].…”
Section: Tap5cs Tabadhmentioning
confidence: 61%
“…Plant dry weight and leaf area were significantly reduced, ΦPSII and increased ΦNPQ, higher photosynthetic rate and stomatal conductance [143] Based on our review of previous studies, we found that in general, plants change the extent of DNA methylation in response to drought stress. While two studies in Table 1 showed a genome-wide decrease in DNA methylation levels [122,125], and six studies showed an genome-wide increase in DNA methylation levels [124,128,136,139,140,142], an increase or decrease in methylation levels of the internal part of promoters of drought response genes was specifically determined by the positive or negative regulation of the gene under drought stress [126,127,130,134,135,137,140,143]. The proportion of methylation changes in response to drought mostly ranged from 10 to 20%, but some showed only slight changes, which may be related to tissue specificity [144].…”
Section: Tap5cs Tabadhmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought is a factor that significantly disrupts physiological processes in plants (inhibits germination, reduces growth, lowers yields, and interferes with key metabolic processes) (Maksimović et al, 2021;Megala et al, 2022). Its influence is more evident during the reproductive stage than other growth stages, and yields are significantly decreased (Atta et al, 2022;Rehman et al, 2021). The severity, duration, type of plant species, and stage of development affect how plants react to drought stress.…”
Section: Introductionmentioning
confidence: 99%